13C-aminopyrine demethylation is decreased in cirrhotic patients with normal biochemical markers - Afolabi, Paul; Wright, Mark; Wootton, Steve A.; Jackson, Alan A. (Isotopes in environmental and health studies, 2013)
This study determined the rates of ¹³C-aminopyrine metabolism in patients with varying degrees of liver cirrhosis as defined by clinical scores. Twenty-five cirrhotic patients and 18 healthy subjects underwent a ¹³C-aminopyrine breath test. The cumulative per cent dose recovery (cPDR) of ¹³C on breath expressed as a percentage of the administered dose at 2 h was significantly lower in cirrhotic patients than in healthy subjects (median: 1.7% versus 9.0%; p <.0001). Significant inverse associations between cPDR at 2 h and the model for end-stage liver disease score, Child–Pugh score, international normalised ratio and bilirubin (all p <.05), but not alanine aminotransferase or alkaline phosphatase were observed in the cirrhotic patients. Taking each biochemical marker independently, cirrhotic patients with normal biochemistry had a significantly lower cPDR at 2 h than healthy subjects (all p <.05). Differences in ¹³C-aminopyrine metabolism were evident in cirrhotic patients with less severe disease and may mark hepatic dysfunction when conventional biochemical markers appear unchanged.